Boosting Grassland Output and Lowering Methane Emission by Grazing Dairy Cows on Diverse Pastures? - Martin Komainda; Friederike Riesch; Johannes Isselstein (Food and Energy Security)
ABSTRACT Implementing phytodiverse grassland may benefit producers through improved herbage production when compared to reference grassland with fewer plant species and may reduce enteric methane emissions of ruminants. Available knowledge of the effect of diverse grassland on dairy cow milk production is contradictory, and influences of species diversity or composition are not precise enough to make valid statements on required species or proportions to improve milk production. The aims of the current study were therefore to evaluate effects of diverse grassland on dairy cow milk production, methane emissions, and forage nutritive value under grazing. Based on 16 eligible studies, we conducted a meta‐analysis. In these studies, swards of diverse vs. reference grassland differed in the proportion of grass (0.38 vs. 0.69) and of dicotyledonous non‐legumes (0.33 vs. 0.026). We found no differences in milk production or methane emissions related to sward type. Plant species that are expected to reduce methane emissions only occurred in very small proportions in the herbage dry matter. Our hypothesis that the milk production of cows grazing diverse grassland instead of simple reference swards is higher and methane emissions lower is thus neither rejected nor confirmed. Milk production correlated positively with legume proportion, which did not differ between sward types. Overall, the analysis revealed that 63% of the studies lasted 10 days or less. Consequently, there is a need for more full‐year and multi‐year dairy cow grazing system studies on diverse grassland to account for variation in grassland primary productivity and nutritive value within seasons and among years.